Implementasi metode pembelajaran campuran berbasis sistem manajemen pembelajaran pada pelatihan keperawatan: A literature review - Azizah, Yuni; Hariyati, Roro Tutik Sri (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Technical competency nursing training is the basis for efforts to develop nurse competency, the implementation of which can be modified using the blended learning method or mixed system. The blended learning system combines face-to-face and online learning both virtual synchronously and virtual asynchronously. In accommodating virtual asynchronous learning, one of the learning technologies that can be used is a Moodle-based Learning Management System (LMS).Purpose: To provide views and descriptions of the use of the Learning Management System in nursing training using the blended learning method, analyzing the effectiveness of use, inhibiting and supporting factors, accuracy of target use, and outcomes resulting from LMS-based learning.Method: This research uses a literature review design, namely collecting and analyzing previous literature or research references that have been selected from various sources to become a conclusion on new ideas or a compilation of new ideas. The literature study selection process is based on Preferred Reporting Items for Systematic Reviews (PRISMA-ScR). The literature used in this study is various articles discussing topics with three categories of keywords, namely learning management system (LMS); blended learning; and nursing training. Search for articles via online databases, including Scopus, ProQuest Clinical Key, Ebscohost, and Pubmed. Based on these keywords, they were input using